PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI DAN EFEKTIVITAS SITEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDUAL KARYAWAN PADA PT. RADITYA PUTRA GRAFIKA GRESIK - Devita Selviana Ainul Izati; Sri Rahayuningsih (Gapenas Publisher, 2023)
In this study, the aim was to determine the effect of the effectiveness and quality of accounting information systems on the performance of individual employees, both personally and simultaneously. This type of research is quantitative, the population in this study is employees at PT. Raditya Putra Graphic Gresik, totaling 30 people. The data collection technique uses a purposive sampling technique (a sample purchase technique with certain considerations). The data were obtained from the results of a questionnaire that was distributed to 30 employee respondents at PT. Raditya Putra Graphic Gresik. The data analysis technique is by using Multiple Linear Regression Analysis, Classical Assumption Test, Data Quality Test, Coefficient of Determination Test. Data testing was carried out with the help of the SPSS (Statistical Product and Service Solution 26) program. Based on the results of the study it can be concluded that partially the Effectiveness of Accounting Information Systems (X?) has a significant effect on individual employee performance, while the Quality of Accounting Information Systems (X?) does not significantly influence individual employee performance. Meanwhile, simultaneously the effectiveness of accounting information systems and the quality of accounting information systems have a positive and significant effect on individual employee performance at PT. Raditya Putra Graphic